PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ETNOMATEMATICA MENGGUNAKAN MODEL RME UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V SD - Ahmad landong; Kintan Muthia Suci; Asya Afrida; Dini Aulia; Indah Sekar Wangi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop a mathematics learning media based onethnomathematics using the Realistic Mathematics Education (RME) approach,integrating the local culture of the Bagas Godang traditional house. The researchemployed a Research and Development (R&D) method using the ADDIE model,which consists of five stages: analysis, design, development, implementation, andevaluation. The research subjects were fifth-grade students at SD IT Riadhul Habibi.The results indicate that the developed media is valid based on evaluations bymedia experts, material experts, and test item experts, and received positiveresponses from both teachers and students. Furthermore, the media effectivelyenhanced students' critical thinking skills, as evidenced by significant improvementsin pretest and posttest scores, with high N-Gain values. Incorporating local culturalelements into the learning media made mathematics learning more contextual,meaningful, and engaging. However, some limitations remain, such as the lack ofwritten educational information and the absence of usage guidelines. Therefore,further development is recommended to refine the media and expand its applicationacross more diverse educational settings.